Portrait of a leader in immunotherapeutics: A passion for biotechnology - Strohl, William R. (Landes Bioscience, 2012)
I recently said to Lila, my wife of 25 years, that I had just realized that “science defined my life”. She responded by telling me that she knew that 25 years ago… The story, though, is that it might not have been, and the journey to get to where I am today was a highly circuitous one, taking me places I never thought I would see. Nevertheless, today I can look back on a career as a scientist that has been both fascinating and fulfilling, and…, perhaps the only life I could have lived in complete happiness. My only hope is that, before my career is over, I can give back as much or more than I have received from science.